Experiment to Recover Tritium from Li-Pb Blanket and Understanding Chemistry of the Li17Pb83–H System. (3rd October 2017) - Fukada, Satoshi; Kinjyo, Mao; Oda, Takuji; Nishikawa, Terunori; Katayama, Kadzunari
Abstract: Various properties of Li-Pb eutectic alloys have been reported aiming at adopting the tritium breeder for the next-step fusion reactor, DEMO. Relations among several physical or chemical properties are reinvestigated here based on not only macroscopic views of the H isotope solubility in Li-Pb and the chemical activity of Li and Pb atoms in the alloy but also a microscopic view on the state of being of H and Li atoms in alloy based on the 1 st principle molecular dynamic (MD) numerical calculation. The Sieverts' constant of H dissolved in Li-Pb is closely related with the chemical activity of Li in Li-Pb. It is found that H dissolved in Li-Pb eutectic alloy has an ionic Li + -H − bond with a single Li atom independent of other Li or Pb atoms and the Li + -H − ionic bond is isolated from another Li atom surrounded by Pb ones. The isotope effect for the Sieverts' constant is also understood in terms of the state of being of the Li + -H − bond in the alloy. The amounts of inert gases dissolved in the Li-Pb eutectic alloy are evaluated, and it is found that their solubilities are in proportion to the square of the molecular diameter which is estimated from exclusive volume of dissolved gas and consequently with the open space volume among Li-Pb atoms. Two experimental results of hydrogen isotopes recovery are introduced using a permeation window and a Li-Pb and inert gas direct contact method, and mass-transfer coefficients to correlate the overall hydrogen transfer process are determined as a function of diffusivity and flow velocity.